Pendampingan Pengelolaan Sampah dalam Meningkatkan Zero Waste dan Nilai Ekonomi di Pesantren Darussalam II Kencong, Kepung, Kediri - Munif, Achmad; M. Soleh Mauludin (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
The problem of waste that is increasingly accumulating in the Islamic boarding school environment, as is the case at the Darussalam II Kencong Islamic Boarding School, Kepung, Kediri, is a challenge that needs to be addressed immediately. This community service program aims to increase economic value and zero waste. Through the Asset Basic Community Development approach, this community service has an impact on increasing awareness of the importance of good waste management among students, Islamic boarding school administrators and the surrounding community. This awareness continues to lead to changes in behavior in waste management, such as sorting waste, reducing organic waste, and reusing waste so that there is a reduction in the volume of waste disposed of in final disposal sites. The most important impact is an increase in the economic value of Islamic boarding schools through waste management, for example from the sale of recycled waste or processed products from organic waste, as well as environmental preservation and achieving the goal of zero waste